Endothelial to mesenchymal transition is common in atherosclerotic lesions and is associated with plaque instability - Evrard, Solene M.; Lecce, Laura; Michelis, Katherine C.; Nomura-Kitabayashi, Aya; Pandey, Gaurav; Purushothaman, K-Raman; d’Escamard, Valentina; Li, Jennifer R.; Hadri, Lahouaria; Fujitani, Kenji; Moreno, Pedro R.; Benard, Ludovic; et al. (Nature communications, 2016)
Endothelial to mesenchymal transition (EndMT) plays a major role during development, and also contributes to several adult cardiovascular diseases. Importantly, mesenchymal cells including fibroblasts are prominent in atherosclerosis, with key functions including regulation of: inflammation, matrix and collagen production, and plaque structural integrity. However, little is known about the origins of atherosclerosis-associated fibroblasts. Here we show using endothelial-specific lineage-tracking that EndMT-derived fibroblast-like cells are common in atherosclerotic lesions, with EndMT-derived cells expressing a range of fibroblast-specific markers. In vitro modelling confirms that EndMT is driven by TGF-β signalling, oxidative stress and hypoxia; all hallmarks of atherosclerosis. ‘Transitioning’ cells are readily detected in human plaques co-expressing endothelial and fibroblast/mesenchymal proteins, indicative of EndMT. The extent of EndMT correlates with an unstable plaque phenotype, which appears driven by altered collagen-MMP production in EndMT-derived cells. We conclude that EndMT contributes to atherosclerotic patho-biology and is associated with complex plaques that may be related to clinical events. Endothelial to mesenchymal transition (EndMT) is a crucial developmental process that also plays a role in the pathogenesis of some diseases. Here the authors show that EndMT contributes to the development of atherosclerosis in mice and humans, and is associated with complex human plaques that may be prone to rupture.